Urban Education in the United States - Rury, J. author. aut Link
XIII, 352 p.
Keywords: Urban Education in the United States examines the development of schools in the large cities of the USA. John Rury, a well-known historian of education, introduces and highlights the most significant and classic essays dealing with urban schooling in this collection. Urban Education in the United States will provide an introduction to critical themes in the history of city schools and will frame each section with an overview of urban education research during particular periods in US history.